2022
DOI: 10.1111/jpc.16239
|View full text |Cite
|
Sign up to set email alerts
|

Targeted screening for congenital cytomegalovirus: A micro‐costing analysis

Abstract: Aim: We aimed to determine the cost and potential cost-savings of delivering a targeted congenital cytomegalovirus (cCMV) screening programme through a universal newborn hearing screening (UNHS) programme to detect cCMV-related hearing loss in infants from Victoria, Australia. Methods: We completed a micro-costing analysis from a health-care perspective using data from a targeted cCMV screening programme piloted between June 2019 and March 2020. The programme involved collection of saliva samples to test for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…As mentioned above, the vast majority of cCMV goes undiagnosed in the absence of a systematic newborn screening program [17,33]. The major justifications for cCMV screening, therefore, include the direct medical benefits and cost-effectiveness derived from the ability to provide early, beneficial interventions for affected children [33,[40][41][42][43][44][45][46][47]. However, there may also be significant value to families that comes from simply having a diagnosis and avoiding other unnecessary testing [33].…”
Section: Arguments For and Against Newborn Screening For Congenital C...mentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the vast majority of cCMV goes undiagnosed in the absence of a systematic newborn screening program [17,33]. The major justifications for cCMV screening, therefore, include the direct medical benefits and cost-effectiveness derived from the ability to provide early, beneficial interventions for affected children [33,[40][41][42][43][44][45][46][47]. However, there may also be significant value to families that comes from simply having a diagnosis and avoiding other unnecessary testing [33].…”
Section: Arguments For and Against Newborn Screening For Congenital C...mentioning
confidence: 99%
“…It is well known that only a small fraction of symptomatic cases is diagnosed clinically; thus, most infants who could benefit from this treatment do not receive it without cCMV screening [17,33,40]. In contrast, there is concern that screening could lead to overtreatment with antivirals, e.g., for asymptomatic infection Cost and burden to healthcare systems cCMV screening is estimated to be highly cost-effective according to numerous studies [40][41][42][43][44][45][46][47]. This is true for both targeted and universal antiviral approaches, though universal screening appears to be superior due to the large number of children whose postnatal-onset hearing loss is identified earlier [40].…”
Section: Antiviral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that targeted congenital cytomegalovirus (cCMV) screening through saliva polymerase chain reaction (PCR) in infants who fail the universal newborn hearing screening (UNHS) falls within the range between cost neutral and cost saving. 1 We believe that the results of the micro-costing analysis performed by Dr. Gillespie and colleagues might have important implications for clinical practice because this targeted cCMV screening method is not only feasible and acceptable to parents, 2 but also provides the opportunity to start the treatment with oral Valganciclovir within the first month of life, which has been shown to have a favourable effect on long-term hearing and neurodevelopmental outcomes. 3 Therefore, we concur with the authors that early antiviral therapy could prevent or improve hearing loss in children with cCMV, although the choice of this treatment should be a shared decision between parents and paediatricians after discussing the potential benefits and risks.…”
mentioning
confidence: 99%
“…1,2 Umberto Ambrosetti1 1 Department of Clinical Sciences and Community Health, University of Milan 2 Audiology Unit, Department of Specialist Surgical Sciences, Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico, Milan, Italy mirko.alde@unimi.it; umberto.ambrosetti@unimi.it Accepted for publication 6 April 2023.…”
mentioning
confidence: 99%